2020
DOI: 10.2196/17372
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Patient Education for Colonic Polyp and Adenoma Detection: Meta-Analysis of Randomized Controlled Trials

Abstract: Background To improve patients’ comprehension of bowel preparation instructions before colonoscopy, enhanced patient education (EPE) such as cartoon pictures or other visual aids, phone calls, mobile apps, multimedia education and social media apps have been proposed. However, it is uncertain whether EPE can increase the detection rate of colonic polyps and adenomas. Objective This meta-analysis aimed to evaluate the efficacy of EPE in detecting coloni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…Thus far, several traditional pairwise meta-analyses investigating the comparative efficacy between EPIs and SPIs for the quality of BP have been published, and they have demonstrated improved BP [ 13 , 14 , 16 - 18 ]. Moreover, our previous meta-analysis also demonstrated the efficacy of EPIs in increasing the PDR and adenomas detection rate (ADR) [ 19 ]. However, only 2 3-arm randomized controlled trials (RCTs) investigated the comparative efficacy of telephone calls or WeChat versus SMS text messaging for BP in patients receiving outpatient colonoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, several traditional pairwise meta-analyses investigating the comparative efficacy between EPIs and SPIs for the quality of BP have been published, and they have demonstrated improved BP [ 13 , 14 , 16 - 18 ]. Moreover, our previous meta-analysis also demonstrated the efficacy of EPIs in increasing the PDR and adenomas detection rate (ADR) [ 19 ]. However, only 2 3-arm randomized controlled trials (RCTs) investigated the comparative efficacy of telephone calls or WeChat versus SMS text messaging for BP in patients receiving outpatient colonoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, several traditional pairwise meta-analyses investigating the comparative efficacy between EPIs and SPIs for the quality of BP have been published, and they have demonstrated improved BP [13,14,[16][17][18]. Moreover, our previous meta-analysis also demonstrated the efficacy of EPIs in increasing the PDR and adenomas detection rate (ADR) [19]. However, only 2 3-arm randomized controlled trials (RCTs) investigated the comparative efficacy of telephone calls or WeChat versus SMS text messaging for BP in patients receiving outpatient colonoscopy.…”
Section: Introductionmentioning
confidence: 81%
“…96 to improve colonoscopy preparation, 97 for example using visual aids or mobile apps in addition to regular counseling. [97][98][99] Two meta-analyses concluded that enhanced instructions benefit bowel preparation quality and ADR, 100,101 although another meta-analysis acknowledging these benefits, pointed to a possible risk of publication bias. 102 An interesting and possibly useful development may be the use of bowel cleansing devices.…”
Section: Studymentioning
confidence: 99%